Nghiên cứu lý thuyết hóa học lượng tử liên kết hiđro chuyển dời xanh của phức giữa CHCl3 và CDCl3 với SO2 trong pha khí - Trung, Nguyễn Tiến; Huế, Trần Thành; Thọ, Nguyễn Minh (Vietnam Journal of Chemistry, 2014)
The CH(D)Cl3-OSO complexes geometries are studied by high level quantum chemical calculation, MP2/6-31++G(2d,2p). The interaction energies are corrected with ZPE and BSSE. Four complexes are obtained, in which three complexes have point group, Cs, with binding energy about 2.18 - 2.20 kcal.mol-1 and the last has point group C1with energy about 2.16 - 2.17 kcal.mol-1. In all complexes, there is a contraction of the C-H(D) bond, a shift to higher frequency called “blue-shift” of the C-H(D) stretching frequency compared to the CH(D)Cl3monomes. However, there is an apparent increase of the IR intensity. The blue-shifts are 8.4, 5.9 cm-1 in the CHCl3… OSO (C1) and CDCl3… OSO (C1), in good agreement with the experimental results 7 cm-1, 5 cm-1, respectively. The NBO analysis indicates that the H-index is not reason for physical origin of blue-shifting hydrogen bond but the EDT is also reason for the contraction